THE ROLE AND ROLE OF MUSIC IN THE FORMATION OF THE SPIRITUAL AND AESTHETIC PERFECTION OF YOUNG STUDENTS - Asqarova Sohibaxon Muhammadjonovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
the article analyzes the status, problems, and opportunities of using them in the spiritual perfection of the younger generation today, based on the views on the enormous educational-impressiveness characteristics of our ancestors in the formation of artistic-aesthetic and spiritual perfection of the student’s personality in the art of music, scientifically based opinions. In this regard, scientific-based recommendations were put forward, which allow achieving more effective results in the implementation of the educational and educational process.